MODERN APPROACHES TO INDUSTRIAL COOPERATION AND THEIR APPLICATION IN UZBEKISTAN’S ECONOMY (Marketing Journal, 2025)
This article examines global best practices in industrial cooperation and their applicability to Uzbekistan’s economy. It highlights SME clusters, innovation parks, and public -private partnerships as key drivers of competitiveness, technological adoption, and export growth. Recommendations focus on cluster development, digital integration, cooperative supply chains, and international collaboration to enhance Uzbekistan’s SME sector.
Keywords: SME; industrial cooperation; clusters; innovation; technology transfer; export; public -private partnership; digitalization; incubators; supply chains; Uzbekistan; international integration